Liberal Democratic Ideals in Civil Society: Problems and Tasks - Shodmankulova Mubarak Mahamatkulovna (Zien Journals, 2023)
The article highlights the issues of the formation of the rule of law as the main factor in the construction of civil society. Various approaches are analyzed to establish a legal state that guarantees the equality of citizens before the law, the priority of the law, the protection of the interests of society and the safety of the population. And by the author, civil society is a society in which there is a humane democratic legal state, where social relations are rational and fair, regulated by laws that express the will of the people, and where the fluffy fulfillment of laws is ensured, the rights, freedoms and legitimate interests of the individual are guaranteed to be ensured at a high level.
Keywords: liberalism; рublic society; Liberal democratic ideas; discipline